A NEW SPECIES OF OPHIORRHIZA (RUBIACEAE) FROM GREAT NICOBAR ISLAND, INDIA - BALAKRISHNAN, N. P. (REINWARDTIA, 1980)
Ophiorrhiza nicobarica Balakr.is described and illustrated and compared with Ophiorrhiza trichocarpos Bl.